Hydrogel coating for improving biological friction performance of Ti6Al4V surface and construction method of hydrogel coating
By constructing a polyacrylamide/polycyclodextrin/azostyrene acrylamide hydrogel coating on the surface of Ti6Al4V, the problem of insufficient wear resistance and corrosion resistance on the surface of titanium alloy is solved, and bio-friction and corrosion resistance are achieved The improvement and self-healing function extends the life of the implant.
Patent Information
- Application Number
- CN202411328273.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art is difficult to effectively improve the wear resistance and corrosion resistance of Ti6Al4V surface at the same time. Especially in the field of biomedical use, titanium alloy implants are prone to wear and corrosion in body fluid environments, resulting in toxic ion dissolution and reduced biocompatibility.
Polyacrylamide/polycyclodextrin/azostyrene acrylamide hydrogel coating is constructed on the surface of Ti6Al4V through self-assembly means, and free radical polymerization initiator is activated using dynamic host-guest interaction and thermal environment to form supramolecular hydrogel Coating, realizes intelligent self-healing and enhances interface binding, and improves bio-friction and corrosion resistance.
It significantly reduces the wear rate and friction coefficient of Ti6Al4V in simulated body fluids, improves the corrosion resistance of body fluids and biocompatibility, provides self-healing function and better mechanical strength, and extends the life of the implant.
Smart Images

Figure CN119258270A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material surface coating preparation, and relates to a hydrogel coating for improving the biological friction performance of a Ti6Al4V surface and a construction method thereof. Background Art
[0002] At present, Ti6Al4V is the most widely used among medical titanium alloys. As an orthopedic implant, Ti6Al4V has many advantages, such as high strength, light weight, good biocompatibility and excellent corrosion resistance, which make it an ideal material for replacing human bones. In addition, the elastic modulus of Ti6Al4V is close to that of human bones, which helps to reduce the stress shielding effect, thereby promoting the growth and repair of bone tissue. However, Ti6Al4V has poor wear resistance. After being implanted in the human body, it is exposed to the corrosive environment of body fluids. This fluid caused by body fluids weakens the passivation ability of Ti6Al4V, resulting in the dissolution of toxic ions such as Al and V. In addition, toxic ions can also destroy the bioactive behavior between implants and tissues. When joint movement occurs, wear occurs when the Ti6Al4V implant rubs against other materials. Therefore, improving the wear resistance and body fluid corrosion resistance of the Ti6Al4V surface can effectively extend the life of Ti6Al4V implants.
[0003] Research is ongoing to enhance the biological function of the surface by using surface modification technology or to improve the corrosion resistance of titanium alloys by surface treatment technology. Compared with other biomaterials, surface-modified Ti6Al4V implants have excellent physical and mechanical properties, good thermal stability, chemical inactivity and biocompatibility. The acceptability of metal implants has also improved in recent years. However, it is still challenging to graft metal coatings onto metal surfaces. In the field of biomedical materials, functional materials with improved biotribology and corrosion resistance have become a hot topic of research.
[0004] Patent application CN109137036A discloses a composite coating of a ceramic layer grafted with hydrogel on the surface of a titanium alloy and a preparation method thereof. First, the surface of the titanium alloy is textured using a YAG laser puncher, and then a hard ceramic film is generated on the textured titanium alloy surface by micro-arc oxidation. Finally, a polyion complex is prepared on the ceramic film by ultraviolet irradiation. However, the patent application only verifies the biotribological properties of the composite coating, and the friction coefficient is close to 0.3. The research on corrosion resistance is not disclosed, and the bonding strength between the coating and the substrate will also affect the biotribological properties, corrosion resistance and biocompatibility of the titanium alloy surface. Patent CN114246978A provides a method for improving the biotribological properties and corrosion resistance of the titanium alloy surface, and a Fe3O4 / HA coating is constructed on the titanium alloy surface by a self-assembly method. However, the Fe3O4 magnetic material may affect the imaging, and the hard inorganic coating has a high hardness and no self-healing properties.
[0005] Patent CN113384750B provides a method for constructing a composite hydrogel coating on the surface of a titanium alloy that reduces bone tissue wear. A PVA / PAA / GO / PDA composite hydrogel coating is constructed on the surface of a titanium alloy by combining chemical assembly with sol-gel. However, its hydrogel coating cannot self-recover from wear. Patent application CN117737718A discloses a method for improving the biofriction and corrosion resistance of a titanium alloy surface. By means of self-assembly, CS / MXene is grafted on the surface of a titanium alloy to improve the biofriction properties of the titanium alloy and improve the surface corrosion resistance of the titanium alloy. However, chitosan materials have the problem of insufficient strength and easy degradation.
[0006] Based on the above materials, it can be seen that the prior art lacks an effective method that can simultaneously and extremely well improve the wear resistance and corrosion resistance of the Ti6Al4V surface. Summary of the invention
[0007] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a hydrogel coating for improving the biofriction performance of Ti6Al4V surface and a construction method thereof. By means of self-assembly, a polyacrylamide / polycyclodextrin / azobenzene acrylamide hydrogel coating is constructed on the surface of Ti6Al4V to improve the biofriction performance of Ti6Al4V and significantly improve the corrosion resistance and biocompatibility of the Ti6Al4V surface.
[0008] The purpose of the present invention can be achieved by the following technical solutions:
[0009] The present invention provides a hydrogel coating for improving the biofriction performance of Ti6Al4V surface. The raw materials of the hydrogel coating include the following components in percentage by weight: 20% to 40% acrylamide (AM), 2% to 10% polycyclodextrin (PCD), 0.05% to 0.5% azobenzene acrylamide (AZOAM), 0.05% to 0.15% cross-linking agent, 0.2% to 0.5% free radical polymerization thermal initiator, and the balance is water. The cross-linking agent is N,N-methylenebisacrylamide, and the free radical polymerization thermal initiator is ammonium persulfate. The raw materials of the hydrogel coating are subjected to free radical polymerization reaction to obtain a polyacrylamide / polycyclodextrin / azobenzene acrylamide (PAM / PCD / AZOAM) hydrogel coating.
[0010] The present invention also provides a method for constructing the above-mentioned PAM / PCD / AZOAM hydrogel coating, comprising the following steps:
[0011] S1, alkali washing treatment of Ti6Al4V surface;
[0012] S2, silane coupling agent and dopamine hydrochloride grafted on the Ti6Al4V surface after alkali washing;
[0013] S3, dissolving polycyclodextrin and azobenzene acrylamide in water, then sequentially adding acrylamide, a crosslinking agent and a free radical polymerization thermal initiator, stirring evenly and then ultrasonically treating until there are no bubbles, to obtain a precursor aqueous solution of polyacrylamide / polycyclodextrin / azobenzene acrylamide hydrogel coating;
[0014] S4, spin-coating the precursor aqueous solution obtained in step S3 on the surface of Ti6Al4V treated in step S2, polymerizing at a temperature of 45° C. to 70° C. for 3 to 6 hours to form a polyacrylamide / polycyclodextrin / azobenzene acrylamide hydrogel coating on the surface of Ti6Al4V.
[0015] Furthermore, in step S1, mechanical polishing and cleaning with a cleaning agent are performed before the alkaline cleaning treatment, and the cleaning agent is any one of anhydrous ethanol or acetone.
[0016] Furthermore, in step S1, the alkaline washing process is specifically as follows: the Ti6Al4V is immersed in an alkaline solution, the immersion temperature is 10-70° C., and the time is 6-10 hours.
[0017] Furthermore, the concentration of the alkaline solution is 0.5-10 mol / L; the alkaline solution is any one of lithium hydroxide solution, potassium hydroxide solution or sodium hydroxide solution.
[0018] Furthermore, step S2 is specifically as follows: firstly placing the Ti6Al4V after alkali washing in a silane coupling agent solution, then washing and drying, and then immersing in a dopamine hydrochloride solution.
[0019] Furthermore, the mass concentration of the silane coupling agent solution is 20 to 30 g / L; the mass concentration of the dopamine hydrochloride solution is 20 to 30 g / L, and the soaking time is 6 to 24 hours.
[0020] Furthermore, in step S3, the mass percentage of the azobenzene acrylamide in water is 0.1% to 0.9%.
[0021] Furthermore, in step S4, the spin coating thickness of the precursor aqueous solution is 5 μm to 50 μm.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) Based on the dynamic host-guest interaction mechanism of hydrogel and the principle of matching the mechanical properties of the interface between Ti6Al4V and silicon nitride spheres, the present invention uses polymer hydrogel to construct an intelligent self-healing viscoelastic coating on the surface of Ti6Al4V through chemical assembly technology, and uses a thermal environment to activate a free radical polymerization initiator to promote the completion of polymerization of the hydrogel. The constructed supramolecular hydrogel coating realizes the self-repair of the damaged coating through dynamic host-guest interaction. Specifically, the present invention first activates the surface of Ti6Al4V, chemically assembles a grafted adhesion layer on the surface, and enhances the interfacial bonding force between the hydrogel coating and the Ti6Al4V surface. Secondly, acrylamide is used as the core monomer of the hydrogel, a supramolecular host is designed and synthesized, and the guest is used as a synergistic monomer. At the same time, other synergistic monomers are preferably cross-linked in situ, and an intelligent polyacrylamide / polycyclodextrin / azobenzene acrylamide hydrogel coating is formed on the surface of Ti6Al4V through a thermally initiated free radical polymerization method, and the self-repair function of the coating after damage is realized through the reversible dynamic interaction between the host and the guest between polycyclodextrin and azobenzene acrylamide.
[0024] (2) The present invention established a friction system of Ti6Al4V and silicon nitride balls, focusing on the influence mechanism of silicon nitride balls on the lubricity and wear resistance of the hydrogel coating; explored the interfacial tribological behavior and the self-healing ability, wettability and mechanical strength of the coating during the friction process, and based on the research results, determined a method to improve the biofriction and corrosion resistance of the Ti6Al4V surface.
[0025] (3) The present invention constructs a PAM / PCD / AZOAM supramolecular hydrogel coating on the surface of Ti6Al4V by means of self-assembly, thereby improving the biotribological properties of Ti6Al4V, and improving the corrosion resistance and biocompatibility of the Ti6Al4V surface. The overall process is simple and the effect is outstanding. In addition, the present invention also systematically measures the biotribological properties and corrosion resistance of the Ti6Al4V surface under the lubrication of SBF (simulated body fluid). The results show that the PAM / PCD / AZOAM hydrogel coating has a more active role in reducing the friction coefficient and wear rate: it significantly reduces the wear rate of Ti6Al4V in simulated body fluids, significantly reduces the friction coefficient of the friction system, and improves the corrosion resistance of the Ti6Al4V surface.
[0026] (4) The construction method of the supramolecular hydrogel coating of the present invention is simple, stable, and highly controllable, and has good theoretical research value and industrial application prospects. It provides a new idea for effectively improving the biotribological properties of Ti6Al4V and improving the corrosion resistance of the Ti6Al4V surface, which will further broaden the application prospects of this construction method in the field of orthopedic medicine. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The friction performance diagram of the hydrogel coating on the surface of Ti6Al4V in the SBF solution in Examples 1-3 of the present invention and Comparative Examples 1-2, wherein (a) is the real-time friction coefficient, (b) is the average friction coefficient and wear rate, (c) is the Bode impedance, and (d) is the Tafel curve;
[0028] Figure 2 Characterization diagrams of the Ti6Al4V surface hydrogel coatings in Examples 1-3 and Comparative Example 2 of the present invention, wherein (a1) is a microscopic topological structure morphology diagram of the Control hydrogel coating in Comparative Example 2, (a2) is a microscopic topological structure morphology diagram of the DSSB1 hydrogel coating in Example 1, (a3) is a microscopic topological structure morphology diagram of the DSSB2 hydrogel coating in Example 2, (a4) is a microscopic topological structure morphology diagram of the DSSB3 hydrogel coating in Example 3, (b) is a small-angle X-ray diffraction diagram of the DSSB2 hydrogel coating in Example 2, and (c) is a FITR infrared spectrum diagram of the Ti6Al4V surface hydrogel coatings in Examples 1-3 and Comparative Example 2;
[0029] Figure 3 The cell viability diagram of BMSC cells co-cultured with Ti6Al4V and the hydrogel coating thereon for 24h and 72h in Examples 1-3 of the present invention and Comparative Examples 1-2;
[0030] Figure 4It is a wettability diagram of the hydrogel coating on the Ti6Al4V surface in Examples 1-3 of the present invention and Comparative Examples 1-2;
[0031] Figure 5 The rheological test results of the hydrogel coating on the Ti6Al4V surface in Example 2 of the present invention and Comparative Example 2, wherein (a) is an amplitude scan and (b) is a cyclic strain scan;
[0032] Figure 6 This is a photo of the self-healing process of the DSSB2 hydrogel coating in Example 2 of the present invention. DETAILED DESCRIPTION
[0033] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0034] The invention provides a hydrogel coating for improving the biofriction performance of a Ti6Al4V surface. The raw materials of the hydrogel coating comprise the following components in percentage by weight: 20% to 40% acrylamide (AM), 2% to 10% polycyclodextrin (PCD), 0.05% to 0.5% azobenzene acrylamide (AZOAM), 0.05% to 0.15% a crosslinking agent, 0.2% to 0.5% a free radical polymerization thermal initiator, and the balance is water; the crosslinking agent is N,N-methylenebisacrylamide, and the free radical polymerization thermal initiator is ammonium persulfate; the raw materials of the hydrogel coating are subjected to a free radical polymerization reaction to obtain a polyacrylamide / polycyclodextrin / azobenzene acrylamide (PAM / PCD / AZOAM) hydrogel coating.
[0035] The method for constructing the above-mentioned PAM / PCD / AZOAM hydrogel coating comprises the following steps:
[0036] S1, pre-mechanically polishing Ti6Al4V, cleaning with a cleaning agent, the cleaning agent is any one of anhydrous ethanol or acetone, and then alkali washing the surface of Ti6Al4V. The alkali washing process is specifically as follows: immersing Ti6Al4V in an alkali solution, the immersion temperature is 10-70°C, the time is 6-10h; the concentration of the alkali solution is 0.5-10mol / L; the alkali solution is any one of lithium hydroxide solution, potassium hydroxide solution or sodium hydroxide solution.
[0037] S2, first placing the Ti6Al4V after alkali washing in a silane coupling agent solution, then washing and drying, and then immersing in a dopamine hydrochloride solution, grafting the silane coupling agent and dopamine hydrochloride on the surface of the Ti6Al4V after alkali washing; the mass concentration of the silane coupling agent solution is 20-30 g / L; the mass concentration of the dopamine hydrochloride solution is 20-30 g / L, and the immersion time is 6-24 hours;
[0038] S3, dissolving PCD and AZOAM in water, wherein the mass percentage of AZOAM in water is 0.1% to 0.9%. Then, AM, N,N-methylenebisacrylamide and ammonium persulfate are added in sequence, stirred evenly and then ultrasonically treated until there are no bubbles, to obtain a precursor aqueous solution of PAM / PCD / AZOAM hydrogel coating;
[0039] S4, spin-coating the precursor aqueous solution obtained in step S3 on the Ti6Al4V surface treated in step S2, the spin-coating thickness of the precursor aqueous solution is 5 μm to 50 μm, and then polymerizing at a temperature of 45° C. to 70° C. for 3 to 6 hours to form a PAM / PCD / AZOAM hydrogel coating on the Ti6Al4V surface.
[0040] The raw materials and equipment used in the present invention are all conventional raw materials and equipment in the art. In the following embodiments, raw materials or processing techniques, unless otherwise specified, are all conventional commercially available raw materials or conventional processing techniques in the art. For example, the silane coupling agent used is KH550.
[0041] Example 1
[0042] This embodiment provides a hydrogel coating for improving the biofriction performance of Ti6Al4V surface and a method for constructing the same. The specific steps are as follows:
[0043] 1) Medical grade Ti6Al4V was mechanically polished to a surface roughness of 0.2 μm, cleaned three times with acetone and deionized water respectively, dried with argon gas, immersed in a 5 mol / L lithium hydroxide solution at 40 °C for 7 h, and the surface of Ti6Al4V was alkaline washed.
[0044] 2) The Ti6Al4V treated with alkali washing was placed in a 30g / L silane coupling agent solution for reaction for 1h, and a silane film was self-assembled on its surface; then the Ti6Al4V with the silane film assembled on the surface was washed with water, dried, and placed in a 30g / L dopamine hydrochloride solution, and the pH value of the solution was adjusted to 8.5 using tris(hydroxymethyl)aminomethane, followed by magnetic stirring at 100rpm for 18h, and the polydopamine adhesion layer was continuously assembled on the Ti6Al4V surface. Then it was taken out, washed with deionized water three times, dried with argon gas, and placed in a sealed bag for standby use, to obtain Ti6Al4V with a surface grafted with a silane coupling agent and a polydopamine adhesion layer.
[0045] 3) 14.25 mg AZOAM was dissolved in 10 g water dispersed with 1.2 g PCD, and then 4.75 g AM, 12.5 mg N,N-dimethylbisacrylamide, and 50 mg ammonium persulfate were added in sequence. The mixture was stirred evenly at 600 rpm using a magnetic stirrer, and then defoamed in an ultrasonic chamber for 10 min to obtain a precursor aqueous solution of the PAM / PCD / AZOAM hydrogel coating.
[0046] 4) Take 2 mL of the precursor aqueous solution obtained in step 3) and spin-coat it on the surface of Ti6Al4V obtained in step 2). The spin coating thickness is measured to be 9.94 μm using a 3D profilometer using a step method. Then, the spin-coated Ti6Al4V is placed in a polystyrene square box and placed in an oven at 60°C for free radical polymerization for 3 h to form a PAM / PCD / AZOAM hydrogel coating on the Ti6Al4V surface. The hydrogel coating is named DSSB1.
[0047] Example 2
[0048] This embodiment provides a hydrogel coating and a construction method thereof for improving the biofriction performance of a Ti6Al4V surface, which is basically the same as that of embodiment 1, except that step 3) and step 4) are:
[0049] Step 3): 23.75 mg AZOAM was dissolved in 10 g water dispersed with 1.2 g PCD, and then 4.75 g AM, 12.5 mg N, N-dimethylbisacrylamide, and 50 mg ammonium persulfate were added in sequence, and stirred evenly at 600 rpm using a magnetic stirrer, and then defoamed in an ultrasonic chamber for 10 min to obtain a precursor aqueous solution of a PAM / PCD / AZOAM hydrogel coating;
[0050] Step 4): Take 2 mL of the precursor aqueous solution obtained in step 3) and spin-coat it on the Ti6Al4V surface obtained in step 2). The spin coating thickness is measured to be 9.96 μm using a 3D profilometer using a step method. Then, the Ti6Al4V obtained after spin coating is placed in a polystyrene square box and placed in an oven at 60°C for free radical polymerization for 3 hours to form a PAM / PCD / AZOAM hydrogel coating on the Ti6Al4V surface.
[0051] The PAM / PCD / AZOAM hydrogel coating obtained in this example is named DSSB2.
[0052] Example 3
[0053] This embodiment provides a hydrogel coating and a construction method thereof for improving the biofriction performance of a Ti6Al4V surface, which is basically the same as that of embodiment 1, except that step 3) and step 4) are:
[0054] Step 3): 47.5 mg AZOAM was dissolved in 10 g water dispersed with 1.2 g PCD, and then 4.75 g AM, 12.5 mg N, N-dimethylbisacrylamide, and 50 mg ammonium persulfate were added in sequence. After stirring evenly at 600 rpm using a magnetic stirrer, the mixture was defoamed in an ultrasonic chamber for 10 min to obtain a precursor aqueous solution of the PAM / PCD / AZOAM hydrogel coating.
[0055] Step 4): Take 2 mL of the precursor aqueous solution obtained in step 3) and spin-coat it on the surface of Ti6Al4V obtained in step 2). The spin coating thickness is measured to be 9.92 μm using a 3D profilometer using a step method. Then, the spin-coated Ti6Al4V is placed in a polystyrene square box and placed in an oven at 60°C for free radical polymerization for 3 hours to form a PAM / PCD / AZOAM hydrogel coating on the Ti6Al4V surface.
[0056] The PAM / PCD / AZOAM hydrogel coating obtained in this example is named DSSB3.
[0057] Example 4
[0058] This embodiment provides a hydrogel coating and a construction method thereof for improving the biofriction performance of a Ti6Al4V surface, which is basically the same as that of embodiment 1, except that step 3) and step 4) are:
[0059] Step 3): 47.5 mg AZOAM was dissolved in 7 g water dispersed with 1.2 g PCD, and then 4.75 g AM, 12.5 mg N, N-dimethylbisacrylamide, and 50 mg ammonium persulfate were added in sequence. After stirring evenly at 600 rpm using a magnetic stirrer, the mixture was defoamed in an ultrasonic chamber for 10 min to obtain a precursor aqueous solution of the PAM / PCD / AZOAM hydrogel coating.
[0060] Step 4): Take 2 mL of the precursor aqueous solution obtained in step 3) and spin-coat it on the Ti6Al4V surface obtained in step 2). The spin coating thickness is measured to be 7.93 μm using a 3D profilometer using a step method. Then, the spin-coated Ti6Al4V is placed in a polystyrene square box and placed in an oven at 60°C for free radical polymerization for 3 hours to form a PAM / PCD / AZOAM hydrogel coating on the Ti6Al4V surface.
[0061] The PAM / PCD / AZOAM hydrogel coating obtained in this example is named DSSB4.
[0062] Example 5
[0063] This embodiment provides a hydrogel coating and a construction method thereof for improving the biofriction performance of a Ti6Al4V surface, which is basically the same as that of embodiment 1, except that step 3) and step 4) are:
[0064] Step 3): 47.5 mg AZOAM was dissolved in 10 g water dispersed with 1.5 g PCD, and then 6 g AM, 20 mg N, N-dimethylbisacrylamide, and 70 mg ammonium persulfate were added in sequence. After stirring evenly at 600 rpm using a magnetic stirrer, the mixture was defoamed in an ultrasonic chamber for 20 min to obtain a precursor aqueous solution of the PAM / PCD / AZOAM hydrogel coating.
[0065] Step 4): Take 2 mL of the precursor aqueous solution obtained in step 3) and spin-coat it on the Ti6Al4V surface obtained in step 2). The spin coating thickness is measured to be 48.75 μm using a 3D profilometer using a step method. Then, the spin-coated Ti6Al4V is placed in a polystyrene square box and placed in an oven at 60°C for free radical polymerization for 3 hours to form a PAM / PCD / AZOAM hydrogel coating on the Ti6Al4V surface.
[0066] The PAM / PCD / AZOAM hydrogel coating obtained in this example is named DSSB5.
[0067] Example 6
[0068] This embodiment provides a hydrogel coating and a construction method thereof for improving the biofriction performance of a Ti6Al4V surface, which is basically the same as that of embodiment 1, except that step 3) and step 4) are:
[0069] Step 3): 13 mg AZOAM was dissolved in 10 g water dispersed with 0.5 g PCD, and then 3 g AM, 10 mg N,N-dimethylbisacrylamide, and 30 mg ammonium persulfate were added in sequence. After stirring evenly at 600 rpm using a magnetic stirrer, the mixture was defoamed in an ultrasonic chamber for 5 min to obtain a precursor aqueous solution of the PAM / PCD / AZOAM hydrogel coating.
[0070] Step 4): Take 2 mL of the precursor aqueous solution obtained in step 3) and spin-coat it on the Ti6Al4V surface obtained in step 2). The spin coating thickness is measured to be 6.38 μm using a 3D profilometer using a step method. Then, the Ti6Al4V obtained after spin coating is placed in a polystyrene square box and placed in an oven at 60°C for free radical polymerization for 3 hours to form a PAM / PCD / AZOAM hydrogel coating on the Ti6Al4V surface.
[0071] The PAM / PCD / AZOAM hydrogel coating obtained in this example is named DSSB6.
[0072] Comparative Example 1
[0073] The comparative example is set as the medical grade Ti6Al4V obtained by mechanically polishing to a surface roughness of 0.2 μm in Example 1 and washing three times with acetone and deionized water respectively.
[0074] Comparative Example 2
[0075] The difference between this comparative example and Example 1 is only in step 3).
[0076] Step 3): 23.75 mg AZOAM was dissolved in 10 g water, and then 4.75 g AM, 12.5 mg N, N-dimethylbisacrylamide, and 50 mg ammonium persulfate were added in sequence, and stirred evenly at 600 rpm using a magnetic stirrer, and then defoamed in an ultrasonic chamber for 10 min to obtain a precursor aqueous solution of the PAM / AZOAM hydrogel coating;
[0077] The PAM / AZOAM hydrogel coating obtained in this example is named Control.
[0078] The raw materials and usage percentages of the hydrogel coatings of Examples 1-6 and Comparative Examples 1-2 are shown in Table 1 below.
[0079] Table 1 Raw materials and percentages of hydrogel coatings of Examples 1-6 and Comparative Examples 1-2
[0080]
[0081]
[0082] The performance tests of the above Examples 1-6 and Comparative Examples 1-2 are as follows:
[0083] (1) Biotribological performance test
[0084] The biotribological properties of Ti6Al4V with hydrogel coating obtained in Examples 1-6 and Comparative Examples 1-2 in SBF solution were tested by a Bruker UMT-lab friction tester. The upper friction pair was a 6mm diameter silicon nitride ball purchased from Jinzhan Bearing Co., Ltd., with a load of 1N, a reciprocating stroke of 2mm front and back, that is, a total stroke of 4mm, and a frequency of 2Hz.
[0085] The test results are as follows Figure 1 (ab) and Table 2. The results show that the surfaces of DSSB1, DSSB2 and DSSB3 hydrogel samples with Ti6Al4V all exhibit low friction coefficients and wear rates, among which DSSB2 has the lowest friction coefficient and wear rate, with a friction coefficient of 0.067 and a wear rate of 0.36×10 -9 mm 3 / N·m.
[0086] (2) Electrochemical corrosion resistance test
[0087] Using an electrochemical workstation three-electrode system, electrochemical impedance spectroscopy (EIS) analysis and Tafel test were performed on the Ti6Al4V with hydrogel coating obtained in Examples 1-6 and Comparative Examples 1-2 in a simulated body fluid (SBF solution) system. The results are as follows: Figure 1 (cd) and shown in Table 2. Figure 1 (c) In the Nyquist plot in the upper left corner, there is a compressed capacitive arc in the low-frequency region. The radius of the capacitive arc of the Ti6Al4V sample with the self-assembled hydrogel coating is significantly larger than that of the Ti6Al4V sample that has only been cleaned. With the increase of AZOAM concentration, the supramolecular network composed of the synergistic cyclodextrin nanodispersion is enhanced, so that the formed network is denser, the barrier effect of the coating is enhanced, and a maze effect is formed, which can effectively resist the corrosion of ions and prevent changes in its composition and structure that make the electrochemical reaction rate slower. However, with the further increase of AZOAM concentration, the corrosion resistance efficiency of the coating decreases. This may be due to the uneven dispersion of AZOAM in the system due to the excessively high concentration, which aggravates the concentrated electrochemical corrosion. Therefore, compared with DSSB3, DSSB4, and DSSB5, the DSSB2 hydrogel sample has better corrosion resistance.
[0088] Depend on Figure 1 (c) It can be seen that compared with the Ti6Al4V group and the Control group that were only cleaned, the Ti6Al4V samples with PAM / PCD / AZOAM hydrogel coatings (DSSB1, DSSB2, and DSSB3) grafted on the surface have higher corrosion resistance, among which the corrosion resistance of the DSSB2 hydrogel coating is better than that of the other hydrogel coatings. Figure 1 (d) The Tafel curves of the five samples showed a similar change trend. It was calculated that DSSB2 hydrogel had the highest corrosion resistance efficiency, which could reach 90.46%.
[0089] The data of the surface biofriction performance and corrosion resistance of Examples 1-6 and Comparative Examples 1-2 are shown in Table 2.
[0090] Table 2 Surface biofriction performance and corrosion resistance of Examples 1-6 and Comparative Examples 1-2
[0091]
[0092]
[0093] The above results show that Examples 1-3 have better surface biofriction performance and corrosion resistance efficiency, so the samples obtained in Examples 1-3 are further characterized as follows:
[0094] (3) Micromorphology characterization
[0095] Each hydrogel coating sample was freeze-dried for 24 h, and its morphology was observed under a scanning electron microscope after gold spraying. Figure 2 (a2-a4) It can be seen that the PAM / PCD / AZOAM hydrogel coating has a more uniform cross-linked topological network structure.
[0096] (4) Small angle X-ray diffraction (SAXS) test
[0097] The SAXS test was conducted using the Xeuss 2.0 equipment from the French company Xenocs, with a copper target light tube power of 30W and a wavelength of The detector is Pilatus 3R 300K, with a single pixel size of 172μm and a test vector range of 0.26nm. -1 ~13.2nm -1 , the distance from the detector to the sample is 360nm.
[0098] Figure 2 (b) shows the SAXS one-dimensional and two-dimensional data of the DSSB2 hydrogel coating. The SAXS data also confirmed the uniform structural distribution of the DSSB2 hydrogel coating. The diffraction peak appears at , indicating the uniform topological structure at the nanoscale.
[0099] (5) Infrared characterization
[0100] The chemical composition of the hydrogel coating samples in Examples 1-3 and Comparative Example 2 was characterized by FTIR infrared spectroscopy. Figure 2 (c) Infrared data show that from Control to DSSB3, all samples have a peak at 3366 cm -1 and 3180cm -1 There are double peaks, indicating the presence of primary amines, and 1650cm -1 The carbonyl stretching vibration peak is 1594 cm -1 NH bending vibration peak. 1029cm -1 The peak may be olefin CH + Out-of-plane bending vibration, DSSB2 red-shifted to 1288 cm -1 , 2919cm -1 The peak may be olefin CH + Stretching vibration, DSSB2 sample red-shifted to 2927 cm -1 This may be due to the π-π conjugation between azobenzene groups.
[0101] (6) Cytocompatibility characterization
[0102] BMSC cell culture: After rats were killed by cervical dislocation, they were immersed in 75% ethanol for 5-10 minutes, and then transferred to a clean bench after disinfection. The bilateral femurs and tibias were separated aseptically, and the muscle tissue around the femurs and tibias was removed using new scissors and tweezers; the bones were kept intact, and pure bones were retained. The tissues were transferred to a new culture dish containing PBS, and the two ends of the bone shaft were cut off to expose the bone marrow cavity; a syringe was used to absorb the culture medium, and a needle was inserted from one end of the bone to flush the bone marrow (until the bone head was white and translucent), and single-cell suspension was made by repeated blowing. Then, centrifuge the 15 mL centrifuge tube containing the rat bone marrow fluid at 1500 rpm for 5 min; discard the supernatant and resuspend the pellet with complete culture medium; slowly drip the cell suspension resuspended in the culture medium onto the Percoll separation solution diluted with PBS to form a density gradient separation solution; centrifuge at 2000-2500 rpm for 25 min, aspirate the white misty cell layer in the middle layer, add PBS to wash the cells, and centrifuge at 1800 rpm for 5 min; discard the supernatant and retain the cell pellet; resuspend the pellet with complete cell culture medium, count the cell suspension and calculate the density gradient according to 1×10 6 / mL density, and cultured statically in a 37℃, 5% CO2 constant temperature incubator. After the first 2 days, change the medium and discard the non-adherent cells. After that, change the medium every 2-3 days depending on the cell growth. When the cell fusion reaches 80%, digest with trypsin for 1-2 minutes and then subculture. Use the third generation BMSC for cytotoxicity experiments.
[0103] BMSC cytotoxicity experiment: The above BMSC cells were co-cultured with Ti6Al4V and the hydrogel coatings (DSSB1, DSSB2, DSSB3, Control, Ti6Al4V) thereon, and CCK-8 cytotoxicity tests were performed after 24h and 72h, respectively, as follows:
[0104] 1) Prepare BMSC cell suspension and count the cells.
[0105] 2) Inoculate the cell suspension in a 96-well plate, about 100 μL per well, and perform 3 replicates of the same sample.
[0106] 3) Place the 96-well plate in an incubator for pre-culture (37° C., 5% CO 2 ) for a period of time, and allow the cells to adhere for 4 hours.
[0107] 4) Add the stock solution of SBF after the reciprocating wear test to each well of the culture plate.
[0108] 5) Place the culture plate in an incubator and incubate for 24 and 72 hours respectively.
[0109] 6) Add 10 μL of CCK-8 solution to each well and gently shake the culture plate to help mix, trying not to create bubbles.
[0110] 7) Place the culture plate in an incubator and incubate for 1 hour.
[0111] 8) Measure the absorbance (OD) at 450 nm using an enzyme reader.
[0112] Cytotoxicity results such as Figure 3 As shown, each group showed low cytotoxicity after 24h and 72h, and the samples with hydrogel coating were slightly better than Ti6Al4V that was only cleaned. Among them, the OD value of the DSSB2 hydrogel sample was relatively the highest, which may be attributed to the DSSB2 hydrogel coating having an optimal cross-linked network, which makes it dissolve less substances and can more effectively prevent the dissolution of metal ions, which is beneficial to maintaining high cell activity.
[0113] (7) Wettability / contact angle test
[0114] 20 μL of water was dropped onto the surface of the hydrogel coating (DSSB1, DSSB2, DSSB3, and Control) and the Ti6Al4V surface, and the contact angle of each group was calculated using the Contact Angle plug-in of ImageJ, as shown in Figure 4 As shown, it was found that the contact angles of the PAM / PCD / AZOAM hydrogel coating surfaces were smaller than that of the Ti6Al4V surface, indicating that the grafting of the PAM / PCD / AZOAM hydrogel coating on the Ti6Al4V surface gave Ti6Al4V better wetting properties.
[0115] (8) Rheological test
[0116] Thermo Fisher Mars40 rotational rheometer was used, and the rotor adopted a parallel plate measurement system. The DSSB2 hydrogel coating sample in Example 2 and the Control group hydrogel coating sample in Comparative Example 2 were subjected to an amplitude scanning experiment. The results of the amplitude scanning experiment are shown in FIG. Figure 5 As shown in (a), the storage modulus (G′) measured by the amplitude sweep experiment at a constant frequency of 1 Hz is significantly higher than the corresponding loss modulus (G″), confirming that the hydrogel coating has elastic properties. At lower strains (1%), G′ is higher than G″, and at higher strains (1000%), the G′ and G″ values are reversed (i.e., G″ is higher than G′), indicating that the hydrogel has transformed into a sol state and exhibits a flow trend. As the shear stress increases, the two moduli maintain nearly constant values until a specific stress threshold (i.e., yield stress) is reached, at which point the two moduli suddenly cross and the values drop sharply. These numerical points indicate that the hydrogel state transitions to a quasi-liquid state (i.e., local viscous behavior), which may be due to structural collapse caused by the breaking of dynamic bonds. From Figure 5 (a) The results show that the critical strain is 500%, based on which a cyclic strain sweep experiment was designed to verify its self-healing performance.
[0117] The same equipment and rotor as above were used to perform cyclic strain scanning experiments on the DSSB2 hydrogel coating sample in Example 2 and the Control group hydrogel coating sample in Comparative Example 2. The results are shown in Figure 2. Figure 5 As shown in (b), the DSSB2 hydrogel continuously transforms from the gel state to the sol state and from the sol state to the gel state in each cycle; and the recovery response speed of the DSSB2 hydrogel is very fast, the G' value is the same as the previous stage, and the recovery rate is close to 100%, showing instantaneous self-healing and self-recovery. However, the Control hydrogel is not stable, and its G' value decreases significantly after each cycle, which means that the strain alternation causes irreversible plastic damage to the Control hydrogel material, and the disentanglement between the molecular chains caused by the added shear pressure. As the polymer chains begin to arrange along the flow direction, the interactions within and between the chains will decrease. Therefore, the DSSB2 hydrogel system with a reasonable proportion of polycyclodextrin (PCD) can meet the rapid mechanical response of the tribological interface phase and the shear direction; and the cyclodextrin (PCD) nanodispersion strengthens the dynamic reversible cross-linking in the network, responds faster to structural damage, and brings more stable self-healing performance to the DSSB2 hydrogel coating.
[0118] (9) Macroscopic display of the self-healing process
[0119] Cut a 1cm×1cm square DSSB2 hydrogel sample into two equal-sized left and right parts. Take one of them and soak it in 0.1wt.% crystal violet staining solution until it is fully stained. Remove the excess staining solution on the surface. Do not do anything to the other one. Then align the two hydrogels along the cut and let them stand for ten minutes. The results show that the DSSB2 hydrogel has a good self-healing phenomenon and realizes its self-repair function after damage. Figure 6 As shown in the figure, DSSB2 hydrogel can well maintain its healed structure both in the natural state and under tensile stress.
[0120] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A hydrogel coating for improving the biofriction properties of Ti6Al4V surface, characterized in that: The raw materials of the hydrogel coating include the following components in percentage by weight: 20% to 40% acrylamide, 2% to 10% polycyclodextrin, 0.05% to 0.5% azobenzene acrylamide, 0.05% to 0.15% crosslinking agent, 0.2% to 0.5% free radical polymerization thermal initiator, and the balance is water.
2. The hydrogel coating for improving the biofriction performance of Ti6Al4V surface according to claim 1, characterized in that: The cross-linking agent is N,N-methylenebisacrylamide, and the free radical polymerization thermal initiator is ammonium persulfate.
3. A method for constructing a hydrogel coating for improving the biofriction performance of a Ti6Al4V surface as claimed in claim 1 or 2, characterized in that: The steps include: S1, alkali washing treatment of Ti6Al4V surface; S2, silane coupling agent and dopamine hydrochloride grafted on the Ti6Al4V surface after alkali washing; S3, dissolving polycyclodextrin and azobenzene acrylamide in water, then sequentially adding acrylamide, a crosslinking agent and a free radical polymerization thermal initiator, stirring evenly and then ultrasonically treating until there are no bubbles, to obtain a precursor aqueous solution of polyacrylamide / polycyclodextrin / azobenzene acrylamide hydrogel coating; S4, spin-coating the precursor aqueous solution obtained in step S3 on the surface of Ti6Al4V treated in step S2, polymerizing at a temperature of 45° C. to 70° C. for 3 to 6 hours to form a polyacrylamide / polycyclodextrin / azobenzene acrylamide hydrogel coating on the surface of Ti6Al4V.
4. The method for constructing a hydrogel coating for improving the biofriction performance of a Ti6Al4V surface according to claim 3, characterized in that: In step S1, mechanical polishing and cleaning with a cleaning agent are performed before alkaline cleaning, and the cleaning agent is any one of anhydrous ethanol or acetone.
5. The method for constructing a hydrogel coating for improving the biofriction performance of a Ti6Al4V surface according to claim 3, characterized in that: In step S1, the alkaline washing process is specifically as follows: the Ti6Al4V is immersed in an alkaline solution, the immersion temperature is 10 to 70° C., and the time is 6 to 10 hours.
6. The method for constructing a hydrogel coating for improving the biofriction performance of a Ti6Al4V surface according to claim 5, characterized in that: The concentration of the alkaline solution is 0.5-10 mol / L; the alkaline solution is any one of lithium hydroxide solution, potassium hydroxide solution or sodium hydroxide solution.
7. The method for constructing a hydrogel coating for improving the biofriction performance of a Ti6Al4V surface according to claim 3, characterized in that: Step S2 specifically comprises: firstly placing the Ti6Al4V after alkali washing in a silane coupling agent solution, then washing and drying, and then soaking in a dopamine hydrochloride solution.
8. The method for constructing a hydrogel coating for improving the biofriction performance of a Ti6Al4V surface according to claim 7, characterized in that: The mass concentration of the silane coupling agent solution is 20 to 30 g / L; the mass concentration of the dopamine hydrochloride solution is 20 to 30 g / L, and the soaking time is 6 to 24 hours.
9. The method for constructing a hydrogel coating for improving the biofriction performance of a Ti6Al4V surface according to claim 3, characterized in that: In step S3, the mass percentage of the azobenzene acrylamide in water is 0.1% to 0.9%.
10. The method for constructing a hydrogel coating for improving the biofriction performance of a Ti6Al4V surface according to claim 3, characterized in that: In step S4, the spin coating thickness of the precursor aqueous solution is 5 μm to 50 μm.
Citation Information
Patent Citations
Composite coating with ceramic layer grafted with hydrogel on surface of titanium alloy and preparation method of composite coating
CN109137036A
Construction method of titanium alloy surface composite hydrogel coating to reduce bone tissue wear
CN113384750B
Method for improving biological friction and corrosion resistance of titanium alloy surface
CN114246978A
Method for improving biological friction and corrosion resistance of titanium alloy surface
CN117737718A